التهاب السحايا عند الأطفال دراسة وبائية – سريرية – مخبرية - شريتح, أحمد; زاهر, محمد; بوز, ولاء (Latakia University Journal -Medical Sciences Series, 2019)
على الرغم من التطورات في صعيد التشخيص والعلاج, يبقى التهاب السحايا عند الأطفال سبباً رئيسياً للإعاقات العصبية والموت. الأهداف: كان الهدف دراسة وبائيات المرض, والتظاهرات السريرية الأكثر شيوعاً لتفريق النمط الجرثومي عن الفيروسي, وعزل الجراثيم المسببة عن طريق تحليل السائل الدماغي الشوكي. طرائق الدراسة : تمت الدراسة في الفترة بين 1 أيار2005 و 31 نيسان 2006 . كانت عينة الدراسة 90 حالة محققة لتعريف منظمة الصحة العالمية للحالة المشتبهة من قبولات قسم الأطفال بمشفى الأسد الجامعي باللاذقية. تم التشخيص عن طريق دراسة السائل الدماغي الشوكي من الناحية الخلوية والكيمياء الحيوية وتلوين غرام والزرع. النتائج : أظهرت الدراسة أن 25.81 % من العينة كانوا التهاب سحايا من النمط الجرثومي, 74.19 % غير جرثومي ( فيروسي غالباً ). وجدت الحمى بنسبة 100 % في كل أنماط التهاب السحايا, الإقياء 100 % في الجرثومي و52 % في الفيروسي, صلابة النقرة 62.5 % في الجرثومي و 30.43 % في الفيروسي. وجدنا 8 مرضى مصابين بالنمط الجرثومي جميعهم ملقحون ضد المستدمية النزلية, عزلنا مكورات سحائية عند حالة ومكورات رؤية عند أخرى, ولم يُعزل الجرثوم المسبب في 4 حالات 3 منها أخذت صادات حيوية خلال الأسبوع السابق للبزل و الحالة الرابعة لم تأخذ . الخلاصة : يبقى التلقيح الوسيلة الفعّالة للوقاية خاصة عندما يضاف لقاح الرؤيات للبرنامج, وعندما يدخل لقاح السحائيات في سن أبكر . Despite the developments in diagnosis and treatment, childhood meningitis is still a major cause of neurological disabilities and death. The aim was to study the epidemics of this disease, the most common clinical characteristics, and to isolate the caused bacteria by cerebrospinal fluid analysis. The study was conducted during the period of 1 May 2005 to 31 April 2006. We found 90 cases of childhood meningitis admitted to Department of Pediatrics, Al-Assad University Hospital, Lattakia, meeting the definition of the suspected case according WHO (World Health Organization). Diagnosis was made by CSF study (cytology, biochemistry, Gram stain and culture). Results showed 25,81 % were bacterial, 74,19 % non-bacterial (viral) meningitis. Fever was 100 % in all types of meningitis, vomiting 100 % in bacterial, 52 % in viral, neck rigidity 62,5 % in bacterial, 30,43 % in viral. We found 8 patients of bacterial meningitis had been vaccinated against haemophillous influenza, and isolated meningiococci in one case, and pneumococci in another; we did not isolate the bacteria in 4 cases, 3 of which had taken antibiotics and one had not. In conclusion, The vaccination is still an effective method for prevention, especially when pneumococci vaccine is added to the program, and meningiococci vaccine is used at an early age.